2014
DOI: 10.1038/ncomms6040
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-modified covalent triazine frameworks hybridized with carbon nanoparticles as methanol-tolerant oxygen reduction electrocatalysts

Abstract: Covalent triazine frameworks, which are crosslinked porous polymers with two-dimensional molecular structures, are promising materials for heterogeneous catalysts. However, the application of the frameworks as electrocatalysts has not been achieved to date because of their poor electrical conductivity. Here we report that platinum-modified covalent triazine frameworks hybridized with conductive carbon nanoparticles are successfully synthesized by introducing carbon nanoparticles during the polymerization proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
235
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(248 citation statements)
references
References 51 publications
11
235
0
2
Order By: Relevance
“…Indeed, very recently, Pt-CTF/ carbon nanoparticle composites proved to show a selective activity of electrochemical oxygen reduction reaction (ORR) in an acidic solution even in the presence of a high concentration of methanol (Figure 6c). 57 The reason for this interesting selective catalytic activity could originate from a Schottky metalsemiconductor heterojunction at the Pt/CTF interface, which can facilitate charged surface by a charge transfer and can trigger a different catalytic activity (Figure 7). 5861 …”
Section: Synthesis and Applications Of Ctfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, very recently, Pt-CTF/ carbon nanoparticle composites proved to show a selective activity of electrochemical oxygen reduction reaction (ORR) in an acidic solution even in the presence of a high concentration of methanol (Figure 6c). 57 The reason for this interesting selective catalytic activity could originate from a Schottky metalsemiconductor heterojunction at the Pt/CTF interface, which can facilitate charged surface by a charge transfer and can trigger a different catalytic activity (Figure 7). 5861 …”
Section: Synthesis and Applications Of Ctfsmentioning
confidence: 99%
“…56,57 For example, platinum coordinated at CTF (Pt-CTF) shows a promising performance as a solid catalyst for direct low-temperature oxidation of methane to methanol with high selectivity, activity, and stability. This catalyst shows a turnover frequency of ca.…”
Section: Synthesis and Applications Of Ctfsmentioning
confidence: 99%
“…9 The abundant nitrogen atoms provide coordination sites, making CTFs attractive catalyst supports for metals. [9][10][11][12][13][14][15][16][17][18][19][20] CTFs have also been applied as solid base catalysts for the conversion of CO 2 21 and as metal free catalysts for ORR. 22,23 The high surface area and nitrogen amount make CTFs attractive for the storage of gases 6,[24][25][26][27][28] or generally as sorbent materials.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular catalysts are usually used as homogeneous catalyst in solution and are difficult to be separated from reactants and products after the reaction. It is very difficult to prepare single atom catalysts and to maintain their structures from aggregation without proper supports [9]. We have recently proposed that these problems can be overcome by confining a metal complex on and within molecular layers forming "confined molecular catalyst", which acts as heterogeneous catalysts, and reported that a Pt complex confined within viologen layer constructed on Si(111) electrode can act as electrocatalysts for both hydrogen evolution [10,11] and CO 2 reduction [12], demonstrating the effectiveness of the "confined molecular catalyst".…”
Section: Introductionmentioning
confidence: 99%